ARCHAEOLOGICAL REVIEW OF THE ROOFS OF BANTAENG COLONIAL BUILDINGS: ITS SHAPE AND TYPOLOGI - Nfn, Hasrianti; Duli, Akin; Tahir Muda, Khadijah; Rosmawati, Rosmawati; Hasanuddin, Hasanuddin; Nur, Muhammad (JURNAL ILMU BUDAYA, 2023)
The roof is one of the elements that can mark a colonial building. Related to this, there is an interest to studying the roofs on colonial buildings in Bantaeng, from the archaeological perspective, specifically the shape and type of roof used and its supporting elements. The benefit and purpose of this study are to provide additional information that is expected to enrich knowledge about the shape and typology of building roofs during the Dutch colonial period in South Sulawesi and Indonesia . This study was carried out using a qualitative approach and an inductive reasoning model. The data collection method is carried out by the desk research, through examination of data and pieces of information analysis using secondary data. The results of the study show a rich variety of roof shapes and typologies, with decorative elements includings dormer, gable, gablevent, roof trim, geveltoppen, nok acroterie, windwijzer, schoor, and tower.